ADDrift traditional painting as a medium in illustrating the narratives of women with Attention Deficit Disorder (ADD) or Attention Deficit Hyperactivity Disorder (ADHD) in Davao City - Tejero, Sophie Marian M. (2023)
ADDrift? is an artistic research that explored the possibilities of traditional painting as a form of visual and health communication in illustrating the lived experience of women diagnosed with ADHD or ADD. The artworks intend to capture how ADHD manifests in the respondents? daily lives, and how it eventually affects their self-esteem and ultimately, their self-concept. These narratives were derived from women between ages 18-44 years old who are clinically diagnosed with ADHD who are residing within Davao City. Yang and Hsu?s (2017) Narrative Design Model was utilized to transform the respondents? narratives from words to symbols which are utilized in the final artworks. The input of stories was processed through three different dimensions: narrative statement, symbolic instantiation, and the dimension of technique. Roland Barthes? concept of visual semiotics, specifically, connotative, and denotative meanings, together with anchorage and relay, also guided in the translation of symbolic elements of the paintings. As a result of these methods (4) four paintings were exhibited in the University of the Philippines Mindanao campus, which served as avenue for spreading awareness and opening safe spaces for ADHD conversations. The entire study acted as a visual representation of the dynamic identities, experiences, and realities of women diagnosed with ADHD as opposed to the pervasive misrepresentation within the Philippine media scene.